A study of the rabbit eye test system to determine the activity of acidic non-steroidal anti-inflammatory agents - Wiseman, Ian Charles (Rhodes University, Faculty of Pharmacy, Pharmacy, 1977)
From introduction : "Inflammation per se, has been defined sufficiently to permit a rational approach to the search for drugs that modify this process, but satisfactory animal models for most rheumatoid diseases are not available". (Swingle 1974) In the search for new meaningful procedures for the detection and evaluation of anti-inflammatory drugs, the rabbit eye as a test system was studied.
Keywords: Nonsteroidal anti-inflammatory agents; Anti-inflammatory agents